Desafios para Moçambique - 2018 - Forquilha, Salvador (Instituto de Estudos Sociais e Económicos, 2018)
PARTE I – POLÍTICA Aptos para Alcançar os seus Objectivos? Obstáculos de ordem administrativa à mobilização da receita local nos municípios Moçambicanos / Armin von Schiller, Salvador Forquilha, Saida Bink, Dominique Klawonn, Jonathan Krull, Alina Sennewald, Conrad Steinhilber e Juliane von Boeselager Urbanização, Serviços Públicos e Recursos Fiscais – Os Principais Desafios para as Autarquias Moçambicanas. Uma análise com enfoque às transferências fiscais intergovernamentais / Abdul Ilal e Bernhard Weimer Uma Economia Política da Reforma Eleitoral em Moçambique / Marc De Tollenaere Estudos Eleitorais em África. Desafios teóricos, metodológicos e conceptuais / Zefanias Matsimbe Alfabetismo Político entre Moçambicanos Alfabetizados. Digitalização e erosão da participação política / Ilídio S. Nhantumbo PARTE II – ECONOMIA Teste à Vontade de Consolidação Fiscal Orçamental em Moçambique. O problema da desorçamentação / António Francisco e Ivan Semedo Efeitos Macroeconómicos da Dívida Pública e do Serviço da Dívida. Uma análise empírica de Moçambique / Yasfir Ibraimo Desenvolvimento Industrial em Contexto de Integração Económica Regional. O caso do sector de equipamentos e serviços industriais em Moçambique e na África do Sul / Epifânia Langa e Maria Nkhonjera Geração de Emprego e Bem-estar. Que contradições existem à luz da agro-indústria em Niassa? / Rosimina Ali A Questão da Terra e os Debates sobre Opções de Transformação Agrária e Rural em Moçambique / Carlos Muianga PARTE III – SOCIEDADE Evolução da Pobreza e do Bem-estar em Moçambique, 1996/97-2014/15 / Channing Arndt, Finório Castigo, Maimuna Ibraimo, Sam Jones, Kristi Mahrt, Vincenzo Salvucci, Ricardo Santos e Finn Tarp Vítimas da Riqueza? A reprodução da pobreza em zonas de minerção / Michael Sambo Relações Laborais e Movimentos de Protesto no Sector do Açúcar / Uacitissa Mandumele Desigualdades de Género em Contextos Rurais em Moçambique. Estudos de caso em localidades na província de Nampula / Aleia Rachide Agy PARTE IV – MOÇAMBIQUE NO MUNDO Acordos de Protecção de Investimentos dos BRICS na África: Mais do mesmo? / Ana Garcia, Yasmin Bitencourt e Bárbara Dias A Transferência de Tecnologia do Brasil para Moçambique para a Fabricação Local de Medicamentos Genéricos: Condições históricas e práticas de uma cooperação em saúde e tecnologia / Ali Brossard Antonielli Migração, Movimento e Urbanização em Angola e Moçambique / Cristina Udelsmann Rodrigues Os Homens e as Mulheres pelo Mundo: O factor humano na ajuda ao desenvolvimento em Moçambique / Marc De Tollenaere
Keywords: *indexed; G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico; politics / política; society / sociedade

The Evidence Is In: How Should Youth Employment Programs In Low-Income Countries Be Designed? - Fox, Louise; Kaul, Upaasna (Policy Research Working Papers, 2018)
Youth in many low-income countries are entering the labor force in unprecedented numbers, yet many struggle to secure rewarding livelihoods. This paper outlines the economic development challenges that constrain youth's transition into employment, and it parses the evidence on which programs and policies appear to speed that transition. It concludes that it may be time for a fundamental reassessment of approaches for addressing youth employment and the youth transition in low-income countries. Employment opportunities in low-income countries reflect the pace of economic and structural transformation. In designing strategies, policies, and programs to meet the entry-into-employment challenge for youth, the starting point is to diagnose the economy and current/future employment opportunities. Combined with the analysis of youth employment problems from a structural transformation perspective, evidence from rigorous evaluations of youth employment interventions provides new insight into which kinds of interventions are more likely to help youth succeed in certain contexts. The evidence reviewed here casts serious doubt on the efficacy and value of training interventions to help youth enter formal wage employment. The case is stronger for interventions that speed the transition to self-employment in farming or non-farm household enterprises. Support for development of transferable character skills and social integration among youth through positive youth development programs should be tested further for employment and earnings impacts, perhaps along with cash transfers to youth or access to finance. In reviewing the evidence on the cost-effectiveness and sustainability of youth employment impacts, the paper also notes the need for better measures of displacement and general equilibrium effects.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico; employment / emprego; youth / juventude